Priming mechanisms providing plants and microbes access to mineral-associated organic matter. (July 2021) - Jilling, Andrea; Keiluweit, Marco; Gutknecht, Jessica L.M.; Grandy, A. Stuart
Abstract: Mineral-associated organic matter (MAOM) is considered a stable reservoir for soil nutrients that influences long-term soil carbon (C) and nitrogen (N) dynamics. However, recent experimental and theoretical evidence shows that root exudates may mobilize MAOM, thereby providing plants and microbes access to a large and N-rich pool. Given the mechanisms underlying MAOM C and N mobilization remain largely untested, we examined direct and indirect pathways by which root exudates destabilize this nutrient pool in laboratory mesocosms. We simulated root exudation with 13 C-labeled oxalic acid to test whether root exudates are directly capable of mobilizing MAOM from mineral surfaces; and with 13 C-labeled glucose to test whether indirect stimulation of microbial and extracellular enzyme activity leads to MAOM decomposition. We also tested the potential for oxalic acid and glucose to mobilize MAOM in an additional subset of sterilized soils to clarify the potential for non-microbial pathways of MAOM destabilization. Over the course of the 12-day MAOM incubation with and without simulated exudates, we measured C cycling (CO2 respiration rates, 13 C–CO2 efflux), N cycling (inorganic N pools, gross N mineralization) and related microbial processes (enzyme activities and microbial community composition via phospholipid fatty acid analysis). Both of the simulated root exudates enhanced MAOM-C mineralization, with cumulative respiration increasing 35–89% relative to the water-only control. Likewise, glucose additions enhanced the production of an exo-cellulase and a chitinase by up to 130% and 39%, respectively, while oxalic acid enhanced oxidative enzyme activities up to 91% greater than control rates. We observed a positive association between glucose-induced shifts in enzyme activities, MAOM-C mineralization, and gross ammonification. Oxalic acid additions were associated with initial increases in fungal relative abundance and in sterile soils appeared to stimulate the release of metals and dissolved organic nitrogen into exchangeable pools. Our results indicate that common root exudates, like glucose and oxalic acid, can significantly increase the turnover and potential release of C and N from MAOM through indirect (e.g., enzyme induction) and direct (e.g., mobilization of metal oxides) mechanisms. Highlights: Simulated root exudates mobilized C and N within mineral-associated organic matter. Glucose and oxalic acid additions enhanced MAOM-C mineralization. Glucose additions facilitated microbial, enzyme-mediated mobilization of MAOM. Oxalic acid additions associated with release of organic N and metals from MAOM.